2021
DOI: 10.1002/chem.202102510
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Lithium Plating and Stripping by Using Vertically Aligned Graphene/CNT Channels Decorated with ZnO Particles

Abstract: Lithium (Li) metal is regarded as the ultimate anode material for use in Li batteries due to its high theoretical capacity (3860 mA h g À 1 ). However, the Li dendrites that are generated during iterative Li plating/stripping cycles cause poor cycling stability and even present safety risks, and thus severely handicap the commercial utility of Li metal anodes. Herein, we describe a graphene and carbon nanotube (CNT)based Li host material that features vertically aligned channels with attached ZnO particles (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Several approaches have been proposed to suppress the formation of Li dendrites, including the creation of SEI layers on the surface of the Li anode, [13] replacement of traditional liquidstate electrolytes with solid-state electrolytes, [14] the use of a Li metal alloy as the anode, [15] and use of three-dimensional (3D) frameworks as Li hosts. [16] SEI layers with relatively high mechanical strength can suppress the formation of Li dendrites by creating uniform nucleation sites for Li metal deposition. [13] The solid-state electrolytes that are inert to the anode physically separate the anode from the cathode.…”
Section: Mechanism Of LI Dendrite Growth and Suppressionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several approaches have been proposed to suppress the formation of Li dendrites, including the creation of SEI layers on the surface of the Li anode, [13] replacement of traditional liquidstate electrolytes with solid-state electrolytes, [14] the use of a Li metal alloy as the anode, [15] and use of three-dimensional (3D) frameworks as Li hosts. [16] SEI layers with relatively high mechanical strength can suppress the formation of Li dendrites by creating uniform nucleation sites for Li metal deposition. [13] The solid-state electrolytes that are inert to the anode physically separate the anode from the cathode.…”
Section: Mechanism Of LI Dendrite Growth and Suppressionmentioning
confidence: 99%
“…[30] As a representative example, Geng et al recently prepared a RGO-based composite that features vertically aligned channels from an aqueous suspension of GO and CNTs via an icetemplate method and demonstrated that Li metal can be uniformly deposited in the channels of the material. [16] Figure 3a summarizes the preparation procedure. An aqueous suspension that contained GO, oxidized CNTs, and Zn(OAc) 2 was frozen from the bottom of the container to induce the vertical growth of ice.…”
Section: Carbons With Manmade Oriented Channelsmentioning
confidence: 99%
See 3 more Smart Citations